FRI0473 Mpo-anca positivity is related to interstitial lung disease in systemic sclerosis. (12th June 2018) - Ichimura, Y.; Kawaguchi, Y.; Takagi, K.; Tochimoto, A.; Higuchi, T.; Yamanaka, H.
Abstract : Background: Recently, there were several reports that patients with systemic sclerosis (SSc) showed acute renal failure with anti-neutrophil cytoplasmic antibody (ANCA) positivity. On the other hand, it is also reported that 7%–13% of patients with SSc revealed myeloperoxidase-ANCA (MPO-ANCA) positivity without vasculitis manifestation in 1990s, but their clinical characteristics were unclear. It is also unknown whether ANCA positivity leads to AAV or not in patients with SSc. It is important for physicians to clarify the characteristics of SSc patients with ANCA positivity, and answer the question whether they will shift ANCA-associated vasculitis (AAV). Objectives: To assess the prevalence of ANCA positive patients with SSc, and clarify the characteristics of these patients. Methods: We enrolled the 333 consecutive patients with SSc who visited our clinic during October 2014 to September 2015, all of who were checked MPO-ANCA using fluorescent-enzyme immune-assay. Clinical manifestation and laboratorial data were obtained from medical chart. The data were assessed by chai-square analysis and Welch's t test. Results: Two patients were diagnosed AAV before October 2014. Eight patients (2.4%) revealed MPO-ANCA positivity without vasculitis manifestation. All of MPO-ANCA positive patients were female, and mean age and disease duration were 61.1 years old and 17.2 years, respectively, and there's no statistically significant differences comparing MPO-ANCA negative patients. As a result of evaluating clinical manifestations, we found that patients with MPO-ANCA positivity more frequently had interstitial lung disease than patients without MPO-ANCA positivity (87.5% vs. 36.7%, p<0.01). The clinical characteristics of 8 patients were shown in table 1. Only one patient out of 8 patients with MPO-ANCA positivity newly diagnosed AAV during mean of 33 months follow-up period. Conclusions: The prevalence of MPO-ANCA positivity in SSc patients were lower than previous reports. MPO-ANCA positivity may be related to interstitial lung disease in SSc. MPO-ANCA positive patient may occasionally reveal AAV in the future, and careful observation are needed. Disclosure of Interest: None declared